Systém odměňování zaměstnanců a návrh změn výrobní haly vybrané společnosti - Sedláčková, Aneta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Tato bakalářská práce se zaměřuje na systém odměňování zaměstnanců ve vybrané společnosti. První část práce je věnována teoretickým poznatkům v oblasti odměňování zaměstnanců, které byly čerpány z odborné literatury. Druhá část práce je zaměřená na analýzu stávajícího stavu odměn ve vybrané společnosti, přičemž jsou zohledněny vnitřní a vnější faktory. V poslední části jsou návrhy změny odměňovacího systému, které by měli zvýšit spokojenost a loajalitu zaměstnanců.

This bachelor thesis focuses on the employee remuneration system in a selected company. The first part of the thesis is devoted to the theoretical knowledge in the field of employee remuneration, which was drawn from the literature. The second part of the thesis is focused on analysis of the current status of remuneration in the selected company, taking into account internal and external factors. In the last part, suggestions are made for changes in the reward system to increase employee satisfaction and loyalty
Remuneration System and Proposed Changes Production Halls of the Selected Company
Keywords: Odměňování zaměstnanců; zaměstnanec; zaměstnavatel; spokojenost zaměstnanců; analýza; návrhy; celková odměna; Remuneration of employees; employee; employer; employee satisfaction; analysis; suggestions; total remuneration